2016
DOI: 10.1177/1073191115602553
|View full text |Cite
|
Sign up to set email alerts
|

Objectified Body Consciousness (OBC) in Eating Psychopathology

Abstract: Objectified body consciousness (OBC) appears to play a crucial role in eating and body-related disturbances, which typically emerge during adolescence. The 24-item OBC Scale (OBCS) has been employed in eating disorder (ED) research and school-based adolescent samples, but evidence for its psychometric proprieties exists only in adult (nonclinical) populations. We evaluated (a) the construct validity and reliability of the 24-item OBCS with data collected from 1,259 adolescent girls and boys from the community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 87 publications
(325 reference statements)
0
29
0
Order By: Relevance
“…As the hyper‐focused attention on and consistent monitoring of the body's outward appearance has been suggested to contribute to the discrepancy between actual and ideal body attributes and/or paradoxically magnify perceived body imperfections, self‐objectification and its cumulative effect may play a key role in the acceleration of body discontent, associated affective distress and/or negative self‐evaluation, thereby potentiating meaningful increases in behavioral symptoms of EDs or maintaining existing recurrent symptomatology . According to scholars, when individuals with EDs or regular behavioral symptomatology continue to think of and monitor their own body's appearance from a third‐person perspective, factors that contribute significantly to pathogenic eating (i.e., body dissatisfaction, negative affectivity) remain untouched .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the hyper‐focused attention on and consistent monitoring of the body's outward appearance has been suggested to contribute to the discrepancy between actual and ideal body attributes and/or paradoxically magnify perceived body imperfections, self‐objectification and its cumulative effect may play a key role in the acceleration of body discontent, associated affective distress and/or negative self‐evaluation, thereby potentiating meaningful increases in behavioral symptoms of EDs or maintaining existing recurrent symptomatology . According to scholars, when individuals with EDs or regular behavioral symptomatology continue to think of and monitor their own body's appearance from a third‐person perspective, factors that contribute significantly to pathogenic eating (i.e., body dissatisfaction, negative affectivity) remain untouched .…”
Section: Discussionmentioning
confidence: 99%
“…The 6‐item Low Self‐Esteem Scale of the Italian validated ED Inventory‐3 ( α Τ1,T2 = 0.89) and the 8‐item Body Surveillance Subscale of the Italian validated Objectified Body Consciousness Scale ( α Τ1,T2 = 0.89) were used to measure low self‐esteem and participant's self‐objectification tendency, respectively. The 10‐item Negative Affect Subscale of the Italian validated Positive and Negative Affect Schedule ( α Τ1 = 0.91; α Τ1 = 0.92) was administered to assess negative affectivity over the past month.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the literature that has examined social pressure has centered upon women and the consequences of searching for ideal of feminine beauty associated with thin-bodied models (Cusumano and Thompson 1997;Thompson and Stice 2001;Thompson et al 2004). This may be explained by the fact that women are more likely to be the targeted by their peers and the media to have "perfect bodies" compared with men leading to more negative consequences (e.g., eating disorders) among women than in men (Dakanalis et al 2017). Despite this assumption, evidence demonstrates that men also feel sociocultural pressure to achieve socially accepted standards of beauty (Karazsia and Crowther 2008;Ricciardelli and McCabe 2004;Tylka 2011).…”
mentioning
confidence: 99%
“…Self-objectification the viewing of the self as an object or from another's perspective (Frederickson & Roberts, 1997), has been associated with body dissatisfaction and eating disorder symptomology (Dakanalis et al, 2016;Frederickson & Roberts, 1997), with some studies suggested that body focused shame mediates the relationship between self-objectification and eating disorder symptomology (Noll & Frederickson, 1998). Frederickson and Robert's (1997) self-objectification theory posits that increased objectification is associated with increased self-monitoring and decreased awareness of internal bodily states leading those with higher levels of selfobjectification to be at risk for anxiety, body dissatisfaction, and depression.…”
Section: Body Dissatisfactionmentioning
confidence: 99%